Parental perceptions and awareness of adolescent cyberbullying in Selangor: a mixed method study - Ghazali, Sarah Aqilah (2024)
Background: The widespread use of the internet among adolescents has increased the prevalence of cyberbullying, posing serious risks to their mental and social well-being. Parental understanding of this issue in Malaysia remains underexplored. Objective: This study assesses parents’ perceptions and awareness of cyberbullying, identifies related factors, and explores parents’ experiences in managing cyberbullying incidents in Selangor. Methodology: Using a sequential explanatory mixed-methods design, Phase 1 involved a cross-sectional study using the KEPS-I questionnaire, which was administered to 522 parents of adolescents, selected from eight national secondary schools through a multistage sampling method, and analysed using linear regression to determine factors related to parental perceptions and awareness of cyberbullying. The interphase involved identifying parents whose children had experienced cyberbullying based on Phase 1 findings. Phase 2, designed as a phenomenological study, included in-depth interviews with 12 parents, selected through purposive sampling from Phase 1 respondents and additional respondents recruited via advertisements to achieve data saturation. Thematic analysis was used to explore parents’ lived experiences and insights. Results: The mean (SD) score for overall parental perceptions and awareness was 3.96 (0.44). The highest mean (SD) score was observed in the preventive measures domain, 4.40 (0.47), while the lowest mean (SD) score was in the internet and social media knowledge domain, 3.61 (0.66). Parents’ age (adjusted b = -0.475 95% CI: -0.704, -0.246, p-value < 0.001), ethnicity (adjusted b = -3.035, 95% CI: -5.893, -0.177, p-value = 0.037), and daily use of the internet and social media (adjusted b = 5.670, 95% CI: 0.244, 11.115, p-value = 0.041) were related to their perceptions and awareness of cyberbullying. Four themes emerged: parental responses to cyberbullying, parental self-efficacy in managing cyberbullying, challenges in addressing cyberbullying and strengthening child safety and support against cyberbullying. Conclusion: The study underscores the need for targeted educational initiatives and support systems to empower parents in managing cyberbullying effectively. Findings contribute to policy recommendations aimed at enhancing parental awareness and preventive strategies.